Spatial distribution and potential sources of arsenic and water-soluble ions in the snow at Ili River Valley, China. (May 2022) - Liu, Xin; Li, Yangzi; Ma, Keke; Yang, Liu; Li, Molei; Li, Changxiang; Wang, Ruijie; Wang, Ninglian; Deng, Li; He, Mao-yong; Huang, Huayu
Abstract: Trace elements and water-soluble ions in snow can be used as indicators to reveal natural and anthropogenic emissions. To understand the chemical composition, characteristics of snow and their potential sources in the Ili River Valley (IRV), snow samples were collected from 17 sites in the IRV from December 2018 to March 2019. Inverse distance weighting, enrichment factor (EF) analysis, and backward trajectory modelling were applied to evaluate the spatial distributions and sources of water-soluble ions and dissolved arsenic (As) in snow. The results indicate that Ca 2+ and SO4 2− were the dominant ions, and the concentrations of As ranged from 0.09 to 0.503 μg L −1 . High concentrations of As were distributed in the northwest and middle of the IRV, and the concentrations of the major ions were high in the west of the IRV. The strong correlation of As with F −, SO4 2−, and NO2 − demonstrates that As mainly originated from coal-burning and agricultural activities. Principal component analysis showed that the ions originated from a combination of anthropogenic and crustal sources. The EFs showed that K +, SO4 2−, and Mg 2+ were mainly influenced by human activities. Backward trajectory cluster analysis suggested that the chemical composition of snow was affected by soil dust transport from the western air mass, the unique terrain, and local anthropogenic activities. These results provide important scientific insights for atmospheric environmental management and agricultural production within the IRV. Graphical abstract: Image 1 Highlights: SO4 2− and Ca 2+ are the main anion and cation in the snow. The high concentrations of As pollutant were distributed in the northwest and middle of IRV. Anthropogenic activities provide important contribution for SO4 2−, F −, NO2 − and As in snow samples.